PENGARUH CITRA SEKOLAH DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN ORANG TUA MEMILIH SEKOLAH DENGAN WORD OF MOUTH (WOM) SEBAGAI VARIABEL INTERVENING PADA SMP BRUDER PONTIANAK - Syamsiar, Benus; Pradiani, Theresia; Handarini, Dany Moenindyah (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: This study aims to analyze the influence of school image (brand image) and service quality on parents’ decision to choose a school, with word of mouth (WOM) as an intervening variable, in the context of SMP Bruder Pontianak as an educational institution for their children. The background of this research is a positive phenomenon: despite the growing number of private schools in Pontianak City, each offering various strengths, SMP Bruder Pontianak continues to gain the trust of parents in enrolling their children at the institution. The school consistently meets its target of admitting seven classes annually. Based on preliminary interviews during the student admission process (PPDB) and field observations prior to the study, three main factors emerged as key considerations for parents: school image (brand image), service quality, and word of mouth as an intervening factor.This research adopts a quantitative method with a survey approach, involving 157 randomly selected parents of seventh-grade students. The data were analyzed using regression techniques to test the relationships between independent variables (school image and service quality), the dependent variable (parents’ decision to choose the school), and the intervening variable (word of mouth), with data processing conducted through SPSS 27.The results reveal that school image (brand image) significantly influences word of mouth, but does not directly affect the decision-making process. Service quality, on the other hand, has a positive and significant effect both on word of mouth and on the decision to choose the school. These findings suggest important implications for SMP Bruder Pontianak: to enhance its school image so it becomes a more decisive factor in parents’ school selection, and to optimize service quality to ensure that all stakeholders—especially parents—receive standardized, high-quality services. Additionally, word of mouth serves as a mediating influence through interactions among parents, friends, family members, and others. Keywords: School Image, Brand Image, Service Quality, Word Of Mouth, Decision-                Making In School Selection Abstrak: Penelitian ini bertujuan untuk menganalisa pengaruh citra sekolah (brand image), kualitas pelayanan, terhadap keputusan orang tua memilih sekolah dengan WOM sebagai intervening pada SMP Bruder Pontianak sebagai sebuah Lembaga Pendidikan bagi anak-anak mereka. Penelitian ini memiliki latar belakang atau fenomena objek yang positif dimana dengan banyaknya jumlah sekolah swasta di Kota Pontianak dengan berbagai keunggulan masing-masing, namun SMP Bruder Pontianak tetap mendapat kepercayaan dari masyarakat untuk menyekolahkan anaknya pada lembaga ini. Target penerimaan sebanyak tujuh kelas selalu terpenuhi. Berdasarkan hasil wawancara sederhana pada saat Penerimaan Peserta Didik Baru (PPDB) dan hasil pengamatan dilapangan dan pra penelitian dilakukan, didapatkan ada tiga faktor yang menjadi pertimbangan bagi orang tua yaitu citra sekolah (brand image), kualitas pelayanan, dan word of mouth sebagai intervening. Metode penelitian yang digunakan adalah kuantitatif dengan pendekatan survei yang melibatkan 157 orang tua kelas tujuh dengan teknik acak (random). Data analisis menggunakan regresi untuk menguji hubungan antar variabel bebas (citra sekolah dan kualitas pelayanan) dengan variabel terikat (keputusan orang tua memilih sekolah) dan word of mouth (intervening) dengan pengolahan data menggunakan SPSS 27. Hasil Penelitian menunjukan bahwa Citra Sekolah (brand image) memiliki pengaruh signifikan terhadap word of mouth. Kualitas pelayanan memiliki pengaruh positif dan signifikan terhadap word of mouth dan terhadap keputusan memilih sekolah. Citra sekolah memiliki pengaruh namun tidak signifikan terhadap keputusan memilih sekolah. Temuan ini memunculkan implikasi bagi SMP Bruder Pontianak untuk meningkatkan citra sekolah agar citra sekolah mampu menjadi salah satu faktor keputusan bagi orang tua memilih sekolah, selain itu memaksimalkan kualitas pelayanan agar semua warga sekolah atau orang tua mendapatkan pelayanan standar yang diberikan. Selain itu Word of Mouth telah berperan sebagai mediasi antar orang tua, teman, keluarga dan orang lain. Kata Kunci: Citra Sekolah, Brand Image, Kualitas Pelayanan, Word Of Mouth,                     Keputusan Memilih